LINGUISTIC LANDSCAPE ON GUIDE SIGNS IN PUBLIC SPACES OF EXPO 2020 DUBAI, UNITED ARAB EMIRATES - Fadhillah, Afifah; Triwinarti, Wiwin (UI Scholars Hub, 2023)
This paper analyzes the linguistic landscape on the guide signs in the public spaces of Expo 2020 Dubai, United Arab Emirates, attended by 192 countries worldwide from October 1, 2021, to March 31, 2022. Dubai, UAE's position as the organizer of Expo 2020 Dubai influences language policy in creating a linguistic landscape situation in a location filled with visitors from various national, linguistic, and cultural backgrounds. This study aims to find out how and what is the background of LL in terms of language in the instructions in public spaces at Expo 2020 Dubai using qualitative methods. The researcher uses Landry and Bourhis's (1997) Linguistic Landscape theory. The results of this study indicate that the LL at Expo 2020 Dubai is filled with Arabic and English, which have informational and symbolic functions. The UAE uses Arabic to show its national identity to the international sphere at Expo 2020 Dubai, which communicates in English. This article can be helpful as a new reference or library for readers to increase their knowledge of linguistic landscape studies in Arab countries, especially Dubai, United Arab Emirates.